“Dizque eran compadres el zorro y el quirquincho”: el verbo decir como marcador reportativo y metadiscursivo en el español del noroeste argentino - Chang, Lidia (2018)
This article aims to describe and analyze the features dizque, dice que and dice in spoken stories from Andean Spanish of Northwest Argentina. We will briefly describe how dizque was formed in Peninsular Spanish and we will introduce the theory of evidentiality from Bermúdez (1996). After that, we will  present the two possible ways dizque turns in American Spanish varieties, according to the linguistic situation of each region. Then, we will describe and analyze dizque, dice que and dice in Andean Spanish of Northwest Argentina.  The test will be done considering our investigation in Tilcara, Jujuy, the data found in La encuesta del 21 (1925) and the work done by Vidal de Battini  (1964). Finally, we will present some conclusions.